Molecular detection and identification of Anaplasma and Ehrlichia species in cattle from Turkey - Aktas, Munir; Altay, Kursat; Dumanli, Nazir (Elsevier Gmbh, 2011)
Bovine anaplasmosis is a tick-borne rickettsial disease widespread in tropical and subtropical areas. We investigated the presence and distribution of Anaplasma spp. in cattle from 6 provinces in Turkey. For amplification of the segment spanning the V1 region of the 165 ribosomal RNA (rRNA) gene of Anaplasma species, a reverse line blot (RIB) hybridization assay was performed on 389 blood samples. RLB identified Anaplasma infections in 9.0% (35/389) of the samples. The most frequently found species was A. marginale (11/389, 2.8%), followed by A. centrale (4/389, 1.0%) and A. phagocytophilum (4/389, 1.0%). Eighteen of 35 PCR-positive samples gave positive signals to the catch-all probes, but did not show any response to the species-specific probes tested. Sequencing results of 5 representative amplicons randomly selected from these specimens indicated that 3 were 100% identical to the sequence of A. ovis, and the other 2 sequences were 99.5% identical to the sequence of Ehrlichia sp. Omatjenne strain. The results further confirmed that A. ovis and Ehrlichia sp. Omatjenne infection occurs in cattle populations in Turkey. (C) 2010 Elsevier GmbH. All rights reserved.
Keywords: Anaplasma; Ehrlichia; PCR; RLB; Cattle